Political Utility Management to Develop a Political Marketing Strategy - พรมแก้ว วิเชียร; Permpoon, Athimart; Kenaphoom, Sanya (Academic Journal of Local Development, 2024)
Developing a strategic political marketing plan requires political utility management. Political marketers can effectively prioritize efforts, allocate resources, and optimize overall strategy by methodically evaluating the potential costs and benefits of different campaign actions and tactics. This strategy makes sure that campaigns work for the interests of society as a whole in addition to winning elections, which promotes a stronger and more functional democratic governance system. The purpose of this study is to analyze political marketing strategies based on the concept of political utility. Political marketing strategies based on the concept of political utility include: (1) Political Ethical Conduct, (2) Audience Understanding, (3) Strategic Positioning, (4) Political Message Clarity, (5) Multi-channel Engagement, (6) Data-Driven Decision Making, (7) Agile Adaptation, (8) Issue Advocacy, (9) Coalition Building, (10) Long-term Vision. In conclusion, the results emphasize ethical behavior, audience comprehension, strategic positioning, message clarity, multi-channel engagement, data-driven decision-making, agile adaptation, issue advocacy, coalition building, and long-term vision as essential elements of political marketing strategies based on the idea of political utility. Together, these components highlight how crucial it is to coordinate campaign activities with more general political goals to maximize efficacy and produce long-lasting effects in the domains of elections and governance.